Potential of direct evaporative cooling system under metal plate attachment to wetted pad application - Mohd Syahray Izham, Muhazihat; Nurrina, Rosli; Radhiyah, Abd Aziz; Abdul Aziz, Jaafar (Universiti Malaysia Pahang, 2018)
Direct evaporative cooling (DEC) system, even in the simpler configuration, is concerned with the wet pad design for improving system cooling performance. The performance measure is assessed by the evaporation of the pad liquid content and changes of mainstream flow properties. This article examined a potential DEC design in laboratory scale that incorporates a water-based wet pad with metal plate attachment. The proposed system is modelled by a low speed uniform air flowing over a heated wet pad. The influence of metal thermal conductivity and the surface contact on air temperature and humidity was evaluated. The results shows that efficiency increases nearly 50 % despite poor influence of metal property and contact area on mainflow properties. Increasing contact area of metal plate plays a major role to preserve the cooling efficiency. Since, base pad without metal plate shows superior performance than that of with metal plate due to the loss sensible heat, DEC system must be designed with consideration of providing more homogenous air mixture and preventing the loss sensible heat.